2005
DOI: 10.1007/s00468-005-0015-5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in leaf morphology and anatomy with tree age and height in the broadleaved evergreen species, Eucalyptus regnans F. Muell

Abstract: Relatively little is known about changes in leaf attributes over the lifespan of woody plants. Knowledge of such changes may be useful in interpreting physiological changes with age. This study investigated changes in leaf morphology and anatomy with tree age and height in the broadleaved evergreen species, Eucalyptus regnans. Fully expanded leaves were sampled from the upper canopy of tree ages ranging from 6 to 240 years, and tree heights ranging from about 10-80 m. There were significant changes in leaf for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
96
3
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(106 citation statements)
references
References 55 publications
(67 reference statements)
1
96
3
6
Order By: Relevance
“…SLA and stomata density followed the expected trend and they were the only variables, which showed the higher values in the young stages for studied species. The high SLA values (> 130 cm² g -1 ) in the young stage indicated a higher investment in the photosynthetic tissues regarding the mechanical tissues, since these species were in growth stage, seeking for better light conditions in the canopy or close to it (Poorter 1999;Boeger et al 2006;England and Attiwill 2006). The young stage leaves presented lower stomata density than the adult stage leaves per area unit probably due to more xeric conditions of the layer near the canopy.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…SLA and stomata density followed the expected trend and they were the only variables, which showed the higher values in the young stages for studied species. The high SLA values (> 130 cm² g -1 ) in the young stage indicated a higher investment in the photosynthetic tissues regarding the mechanical tissues, since these species were in growth stage, seeking for better light conditions in the canopy or close to it (Poorter 1999;Boeger et al 2006;England and Attiwill 2006). The young stage leaves presented lower stomata density than the adult stage leaves per area unit probably due to more xeric conditions of the layer near the canopy.…”
Section: Discussionmentioning
confidence: 98%
“…However, morphological variations in the individuals the seedling and adult stages have been little explored. The existing studies about the leaf morphology versus vertical gradient have mainly investigated the seedlings and adult individuals comparatively (Rijkers et al 2000;England and Attiwill 2006;Sanches et al 2010). However, morphological and anatomical adjustments that tree species develop to transpose the vertical light gradient are also important for forest dynamic understanding (Klich 2000).…”
Section: Introductionmentioning
confidence: 99%
“…A similar result was observed in this study. In conifers, the age-and size-dependent increase in LMA (LMA = leaf density × thickness) is primarily associated with enhanced leaf density, whereas both the thickness and density are increased in broadleaved species (England & Attiwill 2006, Juárez-López et al 2008, Niinemets et al 2009). Many studies have reported that agedependent (or size) increases in the LMA were possibly caused by greater water stress in the leaves of large trees (Ambrose et al 2009, Niinemets et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Geralmente, há maior disponibilidade de luz com o aumento na altura da árvore (KING, 1990), enquanto a condutividade hidráulica diminui (ENGLAND; ATTIWILL, 2006;HUBBARD et al, 1999). A redução na condutividade hidráulica pode levar a uma redução na disponibilidade de nutrientes e, todas essas diferentes condições, podem levar a modificações morfofisiológicas nas folhas.…”
Section: Introductionunclassified
“…Posições mais altas na copa de plantas arbóreas podem promover condições com maior intensidade de radiação, menor disponibilidade hídrica e nutricional (DIAS et al, 2007;ENGLAND;ATTIWILL, 2006;HUBBARD et al, 1999;KIRA;YODA, 1989). Segundo Sabbi et al (2010), folhas de plantas de S. terebinthifolius expostas a ambientes com maior intensidade de radiação promovem folhas com menor área foliar e área foliar específica.…”
unclassified